The Nigerian banking sector reforms power and politics - Apati, Seth 1971- (Palgrave Macmillan studies in banking and financial institutions, 2012)
This is the first comprehensive book on the politics and economics of financial sector consolidation in an emerging market in West Africa. It draws on the author's twenty years experience working with multinationals in this oil-rich zone, to address key issues and examine banking reform in one of the world's fastest-growing economies